2021
DOI: 10.1111/ajt.16768
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral immune response after mRNA-1273 SARS-CoV-2 vaccine in liver and heart transplant recipients

Abstract: Recently published studies have found an impaired immune response after SARS‐CoV‐2 vaccination in solid organ recipients. However, most of these studies have not assessed immune cellular responses in liver and heart transplant recipients. We prospectively studied heart and liver transplant recipients eligible for SARS‐CoV‐2 vaccination. Patients with past history of SARS‐CoV‐2 infection or SARS‐CoV‐2 detectable antibodies (IgM or IgG) were excluded. We assessed IgM/IgG antibodies and ELISpot against the S prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
152
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(167 citation statements)
references
References 20 publications
10
152
2
3
Order By: Relevance
“…Thirty studies reported neutralization assay results in addition to anti-SARS-CoV-2 antibody assays [ 34 , 37 , 41 , 48 , 51 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ]. Thirty-one studies provided data on cellular immunity [ 17 , 21 , 22 , 34 , 37 , 41 , 45 , 46 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 72 , [74] , [75] , [76] , [77] , [79] , [80] , [81] , [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies reported neutralization assay results in addition to anti-SARS-CoV-2 antibody assays [ 34 , 37 , 41 , 48 , 51 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ]. Thirty-one studies provided data on cellular immunity [ 17 , 21 , 22 , 34 , 37 , 41 , 45 , 46 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 72 , [74] , [75] , [76] , [77] , [79] , [80] , [81] , [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Höhe neutralisierender Antikörper, welche mit gemessenen Antikörpern gegen das Spike-Protein (häu-figster Antikörpernachweis) korrelieren, scheint mit einer Protektion vor symptomatischer Erkrankung assoziiert zu sein [10]. Weitere Studien untersuchten auch die zelluläre Immunität nach mRNA-Impfung [11,12] [16,17]. Daraus ergibt sich die Frage, ab wann und mit welchen Vakzinen Booster-Impfungen angeboten werden sollten, um Reinfektionen zu verhindern, insbesondere gegen "variants of concern" (VOC), zumal derartige Reinfektionen schwerwiegend verlaufen können.…”
Section: Stand Der Dingeunclassified
“…figster Antikörpernachweis) korrelieren, scheint mit einer Protektion vor symptomatischer Erkrankung assoziiert zu sein[10]. Weitere Studien untersuchten auch die zelluläre Immunität nach mRNA-Impfung[11,12]. Unter 117 Nieren-/Nieren-Pankreas-transplantierten Patienten entwickelten 65 % eine humorale oder zelluläre Immunität, von denen 29,9 % Antikörper und 35 % T-Zellen aufwiesen.…”
unclassified